공리적 설계를 활용한 고객만족형 설계VE 프로세스 개발 - 박인우; 조규만; 현창택; 홍태훈; Park, In-Woo; Cho, Kyu-Man; Hyun, Chang-Taek; Hong, Tae-Hoon (한국건설관리학회 논문집, 10(3), 2009)
Value Engineering(VE) at design phase(so-called Design-VE) becomes quite a compulsory solution for better customer satisfaction, cost reduction, higher product performance, and, eventually, insured predominance in the competition. Unlike intended, however, the customer requirement on Design-VE has not been fully reflected in reality. Furthermore, the Design-VE occasionally does not progress in regular sequence; Preparation for measuring customer requirement - Function analysis - Idea creation. Therefore, this study suggests Axiomatic Design Theory to be adopted in Design-VE process expecting that the functions required by the customer could systematically reflected in VE process. Post-occupancy Evaluation(POE) is also represented as a method to measure and arrange the customer requirements. The customer satisfaction Design-VE process creates ideas defining functions in more detailed, to reflect the concrete user requirement. This approach helps function analysis and idea creation linked closely because function and idea are developed zigzag (i.e. function - idea - function...) in being decomposed into level down. The application of the process proposed by this study will be helpful to improve the customer requirement measurement and clarify a link between functions and ideas. 국내 건설업체들은 비용절감과 성능향상을 통해 고객의 요구를 반영하고자하는 노력의 일환으로 설계단계의 가치공학(Value Engineering, 이하 VE)을 적극적으로 검토하고 있지만, 실제 VE 활동에서는 고객의 요구가 충분히 반영되지 않고 있으며, 고객의 요구를 측정하는 준비단계에서 기능분석, 아이디어 창출단계에 걸친 순차적인 진행 또한 미비한 실정이다. 본 연구에서는 고객의 요구기능이 VE 수행절차에 체계적으로 반영될 수 있도록, 공리적 설계이론(Axiomatic Design Theory)을 설계VE 프로세스에 도입하여 기존의 설계VE 프로세스를 보완하는 고객만족형 설계VE 프로세스를 제안하고자 한다. 고객만족형 설계VE 프로세스는 설계VE와 공리적 설계의 프로세스 및 특성상의 유사성을 바탕으로 두 이론의 연계방안을 정리하고, 기존의 설계VE 프로세스에 공리적 설계 프로세스를 추가.보완하는 형태로 완성한다. 이때 프로세스의 초기단계인 고객의 요구를 측정하고 정리하는 과정에서, 거주 후 평가(Post-occupancy Evaluation)를 활용하는 방안을 제시한다. 설계VE에 거주 후 평가를 활용하기 위해 평가 기준 및 방법을 설정하고, 이를 바탕으로 고객요구 측정 절차를 수립하여 그 절차에 따라 설문을 작성한다. 본 연구의 결과는 지금까지 국내 설계VE 활동에서 미진하였던 고객요구를 적극 반영하고, 기능과 아이디어의 관계에서 기능-아이디어-기능의 지그재그 창출 방법을 통해 기능-아이디어간의 연계를 명확하게 하여, 체계적이고 효율적인 VE활동을 기대할 수 있다.